2018
DOI: 10.1016/j.jmbbm.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and degradation property improvement in a biocompatible Mg-Ca-Sr alloy by thermomechanical processing

Abstract: Magnesium-based alloys have attracted interest as a potential material to comprise biomedical implants that are simultaneously high-strength and temporary, able to provide stabilization before degrading safely and able to be excreted by the human body. Many alloy systems have been evaluated, but this work reports on improved properties through hot extrusion of one promising alloy: Mg-1.0 wt% Ca-0.5 wt%Sr. This alloy has previously demonstrated promising toxicity and degradation properties in the as-cast and ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…In the study all three groups of rats recovered after surgery, and there were no incision infections, rejections, and other related complications, similar to the reports by Griebel [49] and Henderson, et al [50]. This showed that the Mg-1Zn-0.3Zr-2Gd-1Ca alloy implant had good compatibility with rat tissues.…”
Section: Author Contributionssupporting
confidence: 87%
“…In the study all three groups of rats recovered after surgery, and there were no incision infections, rejections, and other related complications, similar to the reports by Griebel [49] and Henderson, et al [50]. This showed that the Mg-1Zn-0.3Zr-2Gd-1Ca alloy implant had good compatibility with rat tissues.…”
Section: Author Contributionssupporting
confidence: 87%
“…It has been proved that plastic deformation not only has good grain refinement effect but also can make the dendritic second phases into small particles in Mg alloys [12][13][14][15], which is beneficial to the enhancement of mechanical properties and corrosion resistance. Plastic deformation, especially severe plastic deformation (SPD), is an effective way to improve mechanical property and corrosion resistance of Mg alloys [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is mainly attributed to: (i) great strength-to-weight ratio, 2 (ii) good resistance to electromagnetic radiation, 3 (iii) availability, 4 (iv) good cast-ability, 5 (v) low density, (vi) good machinability, 1,6,7 (vii) high dimensional accuracy, 8,9 and (viii) good damping properties. 7 Moreover, Mg is the study hot spot in the biomedical application fields mainly attributed to: (i) the good biodegradable property which eliminates the need for secondary removal surgical of implants, 6,10 (ii) the excellent biocompatibility property which rises the rate of bone formation, 11,12 (iii) good mechanical compatibility, 8,13 (iv) low module and density that are close to the human bone GPa and 1.75-2.1 g/cm 3 , respectively) and result reduction of the stress shielding effect. 14,15 However, the low fracture strain and strength of Mg at room temperature due to the HCP structure as well as its high corrosion rate can restrict its extensive application.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, they have beneficial properties for bone forming. 13,9 Ternary Mg-Sr-Ca alloys are a favorable candidate owing to contribution of both Sr and Ca alloying properties in Mg. Furthermore, these ternary alloys have antitumor and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation